Analyzing the Drivers of Clinical Teaching Doctors Performance and Quality of Medical Graduates - Sulistiyana, Catur Setiya; Affandi, Azhar; Djulius, Horas (Wiga : Jurnal Penelitian Ilmu Ekonomi, 2024)
This study uses descriptive verificative approach to determine, analyze, and examine the influence of competence, organizational commitment, and motivation on clinical teaching doctor performance and its implication for quality of medical graduates at the Faculty of Medicine of Association of Indonesian Medical Education Institutions (AIPKI) Region III. This study is carried out using causal explanatory survey to examine the causal relationship between independent, intervening, and dependent variables using path analysis. The research sample is 185 clinical teaching doctors, which is chosen using proportional random sampling. The data obtained is first analyzed for validity and reliability, and is then tested for the hypothesis using path analysis. The findings indicate that competence, organizational commitment, and motivation partially has a positive and significant influence on clinical teachning doctor performance. Furthermore, it is also found that competence, organizational commitment, and motivation simultaneously have positive and significant influence on clinical teaching doctor performance. This implies that when the competence, organizational commitment, and motivation of clinical teaching doctor increase, this will lead to higher performance. In addition, this study found that clinical teaching doctor performance has a positive and significant influence on quality of graduates.